STAKEHOLDER ANALYSIS PADA KEBIJAKAN PEMANFAATAN TELEMEDICINE DALAM MENGHADAPI COVID-19 DI INDONESIA - Bahtiar, Andhi; Munandar, Adis Imam (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The use of telemedicine is one of the strategic policies of the Indonesian government to minimize physical contact between doctors and patients in the fight against the Covid-19 pandemic. Various suggestions, directions and decisions from government elements in implementing the policy are aimed at maintaining public health services, without increasing the potential for Covid-19 transmission in health facilities. However, in the midst of optimism for the success of the policy, various policy makers had doubts, especially regarding the readiness of facilities, the ethical dimensions of medical personnel professionalism, and the potential for the emergence of new capitalism in the health sector. Through the stakeholder analysis method of reviewing the existing literature, this study will map and identify the various stakeholders involved in telemedicine implementation, as well as their power, legitimacy and urgency. This identification aims to analyze the relationship between stakeholders and anticipate any counter-productive efforts to the government's strategy in suppressing the spread of the Covid-19 outbreak. The results of this study indicate that there are at least thirty-one stakeholders involved, including the Indonesian Ministry of Health, the Covid-19 Task Force and the Indonesian Medical Council (KKI) as definitive stakeholders, as well as investors, providers of telemedicine platforms and the pharmaceutical industry as dangerous stakeholders.